PENGERTIAN TAFSIR ILMU AL-QUR'AN - Abdul Wahab Syakhrani; MHD. Qodari Ashidiqi (MUSHAF JOURNAL: Jurnal Ilmu Al Quran dan Hadis, 2023)
The Koran is an eternal source of Islamic law. The Qur'an is like an endless ocean that holds millions of Divine pearls. To achieve it, everyone must swim and dive into the ocean of the Koran. Not all divers get what they want because of their limited abilities. The science of interpretation continues to develop from time to time, in fact many experts have produced interpretations that are in line with the demands of the times in order to confirm the existence of the Qur'an salih li kulli masa wa makan. Because as time goes by, interpretation follows the time and place. There are many methods used in interpretation, including the tahlili, ijmali, muqaran and maudhu'i methods